2019
DOI: 10.1002/ffj.3532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boiling time on the contents of flavor and taste in Lentinus edodes

Abstract: The changes of flavor components during boiling in Lentinus edodes were studied by high‐performance liquid chromatography and gas chromatography‐mass spectrometry in this article. Results showed that nonvolatile flavor components in L. edodes gradually transferred into the soup during boiling. Contents of nonvolatile flavor substances in the soup increased significantly (p < .05) compared with the preboiling period (15 minutes) and gradually maintained a balanced situation with the boiling time extended. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In this study, organic acids were also significantly differential metabolites, which were key components in determining the flavor and taste as well as playing a crucial role in the quality and nutritional value ( 38 , 39 ). Three organic acids were recognized as differential metabolites, including citric acid, D-(+)-malic acid and (R)-3-hydroxy-5-phenylpentanoic acid.…”
Section: Resultsmentioning
confidence: 75%
“…In this study, organic acids were also significantly differential metabolites, which were key components in determining the flavor and taste as well as playing a crucial role in the quality and nutritional value ( 38 , 39 ). Three organic acids were recognized as differential metabolites, including citric acid, D-(+)-malic acid and (R)-3-hydroxy-5-phenylpentanoic acid.…”
Section: Resultsmentioning
confidence: 75%
“…In Li et al. [ 20 ] literature, they also found that 1-octen-3-ol was a typical flavor component in L. edodes . The content of pyrazine in the attractant of T. molitor was relatively high and makes the roast note of the attractant.…”
Section: Resultsmentioning
confidence: 95%
“…The most characteristic volatile compound in L. edodes attractant was 1-octen-3-ol with a mushroom flavor. In Li et al [20] literature, they also found that 1-octen-3-ol was a typical flavor component in L. edodes.…”
Section: Odorous Compounds In Three Kinds Of Attractantsmentioning
confidence: 88%
“…Organic acids impart sourness and astringency independently, hence they also contribute to edible fungi’s complex and unique taste ( 27 , 28 ). By determining the metabolites in S. rugosoannulata , eight kinds of organic acids and their derivatives were found.…”
Section: Resultsmentioning
confidence: 99%